Recepcja literatury polskiej w Chinach: teoria i dzieje - Li Yinan (Postscriptum Polonistyczne)
Polish literature is popular in China. For over a hundred years some 330 works of Polish literature have been published in China along with hundreds of critical works. The article aims at presenting the reception of Polish literature in China, it discusses issues such as: the history of translation, the selection of translated works and translators’ interests, interpretation of the works and their significance for both Polish literature and Chinese society.